Symptoms in unilateral vestibular hypofunction are associated with number of catch-up saccades and retinal error: results from the population-based KORA FF4 study - Aubele, Maria; Grill, Eva; Eggert, Thomas; Schneider, Erich; Strobl, Ralf Andreas; Jahn, Klaus; Müller, Martin; Holle, Rolf; Linkohr, Birgit; Heier, Margit; Ladwig, Karl-Heinz; Lehnen, Nadine (Frontiers in neurology, 2023)
Objective: The presence and intensity of symptoms vary in patients with unilateral vestibular hypofunction. We aimed to determine which saccadic and vestibulo-ocular reflex parameters best predict the presence of symptoms in unilateral vestibular hypofunction in order to better understand vestibular compensation and its implications for rehabilitation therapy. Methods: Video head impulse test data were analyzed from a subpopulation of 23 symptomatic and 10 currently symptom-free participants with unilateral vestibular hypofunction, embedded in the KORA (Cooperative Health Research in the Region of Augsburg) FF4 study, the second follow-up of the KORA S4 population-based health survey (2,279 participants). Results: A higher number of catch-up saccades, a higher percentage of covert saccades, and a larger retinal error at 200 ms after the onset of the head impulse were associated with relevant symptoms in participants with unilateral vestibular hypofunction (= 0.028, = 0.046, and = 0.038, respectively). After stepwise selection, the number of catch-up saccades and retinal error at 200 ms remained in the final logistic regression model, which was significantly better than a null model (= 0.014). Age, gender, saccade amplitude, saccade latency, and VOR gain were not predictive of the presence of symptoms. Conclusion: The accuracy of saccadic compensation seems to be crucial for the presence of symptoms in unilateral vestibular hypofunction, highlighting the role of specific gaze stabilization exercises in rehabilitation. Early saccades, mainly triggered by the vestibular system, do not seem to compensate accurately enough, resulting in a relevant retinal error and the need for more as well as more accurate catch-up saccades, probably triggered by the visual system.
Gesehen am 31.05.2024